'My voice, my choice': Impact of food technology conditions and message framing on sense of agency and purchase intent. (1st February 2023) - Conroy, Denise M.; Errmann, Amy
Abstract: Evaluations consumers apply towards the way food technologies are framed is an important overlooked domain of food communication and advertising. We explore two distinct conditions of food technologies—technologies that manipulate external environments (i.e., robotics) and technologies that manipulate food internally (i.e., gene editing). The current research demonstrates that food manipulated in an external environment (vs. internal manipulation) has higher purchase intent (Study 1). Further, we explore how food technologies may be framed differently in messages to influence consumers' sense of agency. Study 2 demonstrates that food technologies that manipulate the food environment induce a higher sense of agency, whilst in contrast food technologies that manipulate food internally influence a lower sense of agency, impacting purchase intent. Study 3 explores a unique way in which sense of agency can be increased for food technologies with internal manipulations through framing the technology as agency-supportive. Investigating the impact of food technologies and how they may be framed to influence consumer psychology, and more specifically sense of agency, has rarely been explored. However, as food technologies have important upstream consequences on downstream advertising, their role on consumer psychology warrants investigation. Highlights: The research explores technologies that manipulate external environments and technologies that manipulate food internally. Food manipulated in an external environment (vs. internal manipulation) has higher purchase intent. External environment manipulations induce a higher sense of agency and internal manipulations a lower sense of agency. Purchase intent can be increased for technologies with internal manipulations through framing as agency-supportive.